Hak Waris Beda Agama Perspektif Maqashid Syari’ah - Nur Sa’adah Harahap; Nursania Dasopang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the issue of distributing inheritance rights in the context of religious differences among heirs, which is often a complex issue in Islamic law. In traditional fiqh, heirs of different religions are generally not entitled to receive a share of a Muslim's estate. However, the maqashid shari'ah approach, which focuses on the purpose and wisdom of shari'ah, opens up opportunities to reinterpret such rules in light of the principles of justice, beneficence and family harmony. This study aims to analyze how maqashid shari'ah can be applied to provide a solution to the issue of inheritance rights for heirs of different religions. Using normative research methods, this study identifies the relevance of maqashid shari'ah in maintaining social stability, avoiding conflict, and ensuring family welfare. One of the approaches discussed is the application of mandatory wills as a mechanism to provide financial rights to non-Muslim heirs without violating the basic principles of shari'ah. The results show that maqashid shari'ah offers flexibility in addressing contemporary challenges, including the issue of interfaith inheritance. This approach not only emphasizes the importance of maintaining family relationships, but also creates a balance between normative justice and the practical needs of modern society.Thus,maqashid shari'ah becomes a relevant framework to answer inheritance issues in the context of religious differences.